Optimization of Ultrasound-Assisted Extraction of phenolic compounds and anthocyanins from blueberry (Vaccinium ashei) wine pomace - He, Bo; Zhang, Ling-Li; Yue, Xue-Yang; Liang, Jin; Jiang, Jun; Gao, Xue-Ling; Yue, Peng-Xiang (Food chemistry, 2016)
•Bioactive compounds were extracted from byproduct Blueberry Wine Pomace.•Ultrasound-Assisted Extraction technique was optimized for phenolics and anthocyanins recovery.•Ultrasound-Assisted Extraction yielded more than Conventional Solvent Extraction.•HPLC–DAD–MS/MS showed that the two methods yielded the same anthocyanins. Ultrasound-Assisted Extraction (UAE) of total anthocyanins (TA) and phenolics (TP) from Blueberry Wine Pomace (BWP) was optimized using Response Surface Methodology (RSM). A Box–Behnken design was used to predict that the optimized conditions were an extraction temperature of 61.03°C, a liquid–solid ratio of 21.70mL/g and a sonication time of 23.67min. Using the modeled optimized conditions, the predicted and experimental yields of TA and TP were within a 2% difference. The yields of TA and TP obtained through the optimized UAE method were higher than those using a Conventional Solvent Extraction (CSE) method. Seven anthocyanins, namely delphinidin-3-O-glucoside, delphindin-3-O-arabinoside, petunidin-3-O-glucoside, cyanidin-3-O-arabinoside, cyanidin-3-O-glucoside, malvidin-3-O-glucoside and malvidin-3-O-arabinoside, were found in the BWP extract from both the UAE and CSE methods.